Histological Picture in Neocortex and Hypothalamus of Homoio- and Heterothermal Animals Under Artificial and Natural Hypometabolism - Lomako, Viktoriya V.; Shylo, Aleksandr V. (Problems of Cryobiology and Cryomedicine, 2015)
Structural changes in the brain neocortex and hypothalamus in heterothermal hamsters under natural and artificial hypometabolism, and in homoiothermal rats under artificial hypometabolism as well as 2 and 24 hrs later awakening from hypometabolic states were studied. The following changes in the studied brain tissues were observed: a dilation/constriction of perivascular spaces and dark neurons appearance; the emergence of neurons with nucleoli in their nucleus, likely indicating an increased protein synthesis in response to hypoxia. The latter was confirmed by the revealed corresponding fluctuations in the total protein levels in the tissues. The identified changes probably reflect different phases of normal metabolic processes under hypometabolism and are not resulted from either toxic effect or pathological manifestations. The changes were species-specific and manifested differently, both qualitatively and quantitatively, at certain stages of entering and awakening from hypometabolic states. Probl Cryobiol Cryomed 2015; 25(2): 93-103